Building climate-smart fisheries in Australia: insights from climate and ecosystem status reports - Stephanie Brodie; Laura K. Blamey; Alistair J. Hobday; Éva Plagányi; Daniel Corrie; Natalie Couchman; Alice McDonald; Campbell Davies; Ryan A. Downie; J. Paige Eveson; Elizabeth A. Fulton; Jason R. Hartog; et al. (Reviews in Fish Biology and Fisheries, 2026)
Ongoing concerns about the impact of climate change on Australia’s oceans has driven a request from fisheries managers for improved science communication to the seafood sector. Despite these concerns, translating climate science into management and industry action at regional and sectoral scales remains a challenge. We developed a reporting structure for communicating climate and ecosystem status to fisheries management, industry, and research stakeholders. Our reports consider historical climate impacts, ecosystem indices derived from scientific observing programs, anecdotal on-the-water observations from industry, and forecast climate outlooks tailored for the upcoming fishing season. We developed and delivered reports across 10 diverse fishery case studies, spanning multiple spatial scales and regions (from the tropical north to the temperate south and sub-Antarctic islands) and target species (encompassing benthic invertebrates, demersal fish and sharks, and pelagic billfish and tunas). Here, we describe the reporting structure, the climate and ecosystem indices used, as well as key lessons from the development and dissemination of reports. Key lessons include: (1) Developing tailored environmental indices enhances relevance; (2) Ecosystem observations are essential but remain spatially and temporally patchy; (3) Fishery-independent surveys provide vital data; (4) Remote climate drivers must be considered; (5) Seasonal forecasts offer actionable insights for short-term planning; (6) Fisher observations provide context-rich information that should be systematically incorporated. The lessons and general reporting structure can be applied to the development of other climate and integrated ecosystem reporting activities that are ongoing around the world. We contend that these reports serve as important tools for fostering climate resilience and facilitating the adaptation of the Australian seafood sector to the short and long-term challenges of rapidly changing ocean ecosystems.

Incorporating Climate Change Impacts Within Harvest Strategies: An Overview of Approaches - Pia Bessell‐Browne; André E. Punt; David C. Smith; Elizabeth Fulton; Alice McDonald; Mark Dickey‐Collas; Daniel E Duplisea; Melissa A. Haltuch; Pamela Mace; Andrew Penney; Éva Plagányi; Robert Scott (Fish and Fisheries, 2025)
Ensuring that harvest strategies are robust to climate change is a top priority for many fisheries jurisdictions globally. This is because climate change is altering ecosystem structure and the productivity of marine species. We outline a range of approaches for incorporating climate change impacts within harvest strategies, including how a harvest strategy is specified and changes to monitoring requirements. Approaches evaluated include the use of extended stock assessments, multi‐species and ecosystem models, revised management reference points, implementing regime shifts in model parameters, the provision of climate‐sensitive catch advice, projections under alternative climate change scenarios and expanded use of management strategy evaluation. We evaluate the utility of these approaches against cost, data needs and uncertainty criteria; highlight key learnings from a range of global jurisdictions and demonstrate the broad array of options available outside of direct incorporation of climate variables within stock assessments. We identify approaches that have been successfully implemented and show that the most complex responses are not always the most successful. While there is no one‐size‐fits‐all way to incorporate climate change within harvest strategies, we outline the need for flexible management arrangements. We also provide examples of approaches that have been successfully implemented, demonstrating that many of the most data‐intensive responses will only be applicable in a few cases, necessitating the application of cheaper, less data‐intensive approaches that are associated with greater uncertainty.

Ecological network analysis and ecological indicators for an intensively used temperate marine embayment - Lozano-Montes Hector; Neil R. Loneragan; Stephanie A. Fourie; Elizabeth A. Fulton; Daniel Yeoh (Estuarine, Coastal and Shelf Science, 2025)

Transitions to deeply decarbonized transportation and energy systems around the world: challenges and solutions - Lew Fulton; Andreas W. Schäfer; Daniel Sperling (Transportation Research Part D: Transport and Environment, 2024)

Wnt7a Decreases Brain Endothelial Barrier Function Via β-Catenin Activation - Narek Manukjan; Steven Chau; Florian Caiment; Marcel van Herwijnen; Hubert J. Smeets; Daniel Fulton; Zubair Ahmed; W. Matthijs Blankesteijn; Sébastien Foulquier (Molecular Neurobiology, 2024)
The blood-brain barrier consists of tightly connected endothelial cells protecting the brain’s microenvironment from the periphery. These endothelial cells are characterized by specific tight junction proteins such as Claudin-5 and Occludin, forming the endothelial barrier. Disrupting these cells might lead to blood-brain barrier dysfunction. The Wnt/β-catenin signaling pathway can regulate the expression of these tight junction proteins and subsequent barrier permeability. The aim of this study was to investigate the in vitro effects of Wnt7a mediated β-catenin signaling on endothelial barrier integrity. Mouse brain endothelial cells, bEnd.3, were treated with recombinant Wnt7a protein or XAV939, a selective inhibitor of Wnt/β-catenin mediated transcription to modulate the Wnt signaling pathway. The involvement of Wnt/HIF1α signaling was investigated by inhibiting Hif1α signaling with Hif1α siRNA. Wnt7a stimulation led to activation and nuclear translocation of β-catenin, which was inhibited by XAV939. Wnt7a stimulation decreased Claudin-5 expression mediated by β-catenin and decreased endothelial barrier formation. Wnt7a increased Hif1α and Vegfa expression mediated by β-catenin. However, Hif1α signaling pathway did not regulate tight junction proteins Claudin-5 and Occludin. Our data suggest that Wnt7a stimulation leads to a decrease in tight junction proteins mediated by the nuclear translocation of β-catenin, which hampers proper endothelial barrier formation. This process might be crucial in initiating endothelial cell proliferation and angiogenesis. Although HIF1α did not modulate the expression of tight junction proteins, it might play a role in brain angiogenesis and underlie pathogenic mechanisms in Wnt/HIF1α signaling in diseases such as cerebral small vessel disease.

‘Scaling up’ our understanding of environmental effects of marine renewable energy development from single devices to large-scale commercial arrays - Daniel J. Hasselman; Lenaïg G. Hemery; Andrea E. Copping; Elizabeth A. Fulton; Jennifer Fox; Andrew B. Gill; Brian Polagye (Science of The Total Environment, 2023)

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

Probing the oligomeric re-assembling of bacterial fimbriae in vitro: a small-angle X-ray scattering and analytical ultracentrifugation study - Alexandra S. Solovyova; Daniel T. Peters; Gema Dura; Helen Waller; Jeremy H. Lakey; David A. Fulton (European Biophysics Journal, 2021)
Capsular antigen fragment 1 (Caf1) is an oligomeric protein consisting of 15 kDa monomeric subunits that are non-covalently linked through exceptionally strong and kinetically inert interactions into a linear polymer chain. It has been shown that after its thermal depolymerisation into unfolded monomeric subunits, Caf1 is able to efficiently repolymerise in vitro to reform its polymeric structure. However, little is known about the nature of the repolymerisation process. An improved understanding of this process will lead to the development of methods to better control the lengths of the repolymerised species, and ultimately, to better design of the properties of Caf1-based materials. Here we utilize small-angle X-ray scattering to estimate the size of Caf1 polymers during the first 24 h of the re-polymerisation process. Analytical ultracentrifugation measurements were also used to investigate the process post-24 h, where the rate of repolymerisation becomes considerably slower. Results show that in vitro polymerisation proceeds in a linear manner with no evidence observed for the formation of a lateral polymer network or uncontrolled aggregates. The rate of Caf1 in vitro repolymerisation was found to be concentration-dependent. Importantly, the rate of polymer growth was found to be relatively fast over the first few hours, before continuing at a dramatically slower rate. This observation is not consistent with the previously proposed step-growth mechanism of in vitro polymerisation of Caf1, where a linear increase in polymer length would be expected with time. We speculate how our observations may support the idea that the polymerisation process may be occurring at the ends of the chains with monomers adding sequentially. Our findings will contribute towards the development of new biomaterials for 3D cell culture and bio-printing.

Effects of dietary cypermethrin exposure on swimming performance and expression of lipid homeostatic genes in livers of juvenile Chinook salmon, Oncorhynchus tshawytscha - Neil Fuller; Jason T. Magnuson; Kara E. Huff Hartz; Corie A. Fulton; Gregory W. Whitledge; Shawn Acuña; Daniel Schlenk; Michael J. Lydy (Ecotoxicology, 2021)

Morphological predictors of swimming speed performance in river and reservoir populations of Australian smelt Retropinna semoni - Daniel Phillip Svozil; Lee J. Baumgartner; Christopher J. Fulton; Richard Keller Kopf; Robyn J. Watts (Journal of Fish Biology, 2020)
Dam construction is a major driver of ecological change in freshwater ecosystems. Fish populations have been shown to diverge in response to different flow velocity habitats, yet adaptations of fish populations to river and reservoir habitats created by dams remains poorly understood. We aimed to evaluate divergence of morphological traits and prolonged swimming speed performance between lotic and lentic populations of Australian smelt Retropinna semoni and quantify the relationship between prolonged swimming speed performance and morphology. Prolonged swimming speed performance was assessed for 15 individuals from each of three river and two reservoir populations of R. semoni using the critical swimming speed test (U crit ). Body shape was characterized using geometric morphometrics, which was combined with fin aspect ratios and standard length to assess morphological divergence among the five populations. Best subsets model‐selection was used to identify the morphological traits that best explain U crit variation among individuals. Our results indicate R. semoni from river populations had significantly higher prolonged swimming speed performance (U crit = 46.61 ± 0.98 cm s −1 ) than reservoir conspecifics (U crit = 35.57 ± 0.83 cm s −1 ; F 1,74 = 58.624, Z = 35.938, P R. semoni sampled from river populations had significantly higher fin aspect ratios (AR caudal = 1.71 ± 0.04 and 1.29 ± 0.02 respectively; F (1,74) = 56.247, Z = 40.107, P pectoral = 1.85 ± 0.03 and 1.33 ± 0.02 respectively; F (1,74) = 7.156, Z = 4.055, P crit was most strongly correlated with pectoral and caudal fin aspect ratios (R 2 adj = 0.973, AIC c = 41.54). Body shape, however, was subject to a three‐way interaction among population, habitat and sex effects (F 3,74 = 1.038. Z = 1.982; P

Current Status and Future Challenges of Weather Radar Polarimetry: Bridging the Gap between Radar Meteorology/Hydrology/Engineering and Numerical Weather Prediction - Guifu Zhang; Vivek N. Mahale; Bryan J. Putnam; Youcun Qi; Qing Cao; Andrew D. Byrd; Petar Bukovcic; Dusan S. Zrnic; Jidong Gao; Ming Xue; Youngsun Jung; Heather D. Reeves; et al. (Advances in Atmospheric Sciences, 2019)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

A case for redefining the boundaries of the Mesoamerican Reef Ecoregion - Iliana Chollett; Lysel Garavelli; Daniel Holstein; Laurent Cherubin; Stuart Fulton; Stephen J. Box (Coral Reefs, 2017)

Antibiotics as CECs: An Overview of the Hazards Posed by Antibiotics and Antibiotic Resistance - Geoffrey I. Scott; Dwayne E. Porter; R. Sean Norman; C. Hart Scott; Miguel I. Uyaguari-Diaz; Keith A. Maruya; Steve B. Weisberg; Michael H. Fulton; Ed F. Wirth; Janet Moore; Paul L. Pennington; Daniel Schlenk; et al. (Frontiers in Marine Science, 2016)

Transport, degradation and cell wall-integration of XXFGol, a growth-regulating nonasaccharide of xyloglucan, in pea stems - Hildegard M. Warneck; Daniel C. Fulton; Hanns Ulrich Seitz; Stephen C. Fry (Planta, 1997)